The exercise pressor reflex in hypertension - Masaki Mizuno; Jere H. Mitchell; Scott A. Smith (Japanese Society of Physical Fitness and Sports Medicine, 2016)
The cardiovascular response to physical exercise is abnormally exaggerated in hypertension. Since such responses potentially increase the risk for adverse cardiovascular events, it is clinically important to elucidate the cause of this cardiovascular hyper-excitability in this disease. Even if blood pressure is normal at rest, individuals displaying a heightened blood pressure response to exercise are more likely to develop future hypertension. Therefore, early detection of this abnormal circulatory response to physical activity could lead to the early treatment as well as prevention of hypertension. Much evidence suggests that the abnormal exercise pressor reflex (EPR; a reflex originating in exercising skeletal muscle) significantly contributes to the generation of the enhanced circulatory responses in this disease. In addition, it has been demonstrated that the EPR dysfunction is mediated by both mechanically-sensitive fibers associated with the muscle mechanoreflex and chemically-sensitive fibers associated with the muscle metaboreflex. This review focuses on the underlying mechanisms for this overactive EPR function in hypertension. Specifically, updates on our current understanding of the EPR in this disease as well as experimental models used to examine this reflex are presented.